Characteristics of a Baoule herd - Morkramer, G.L.; Dekpol, K. (1984)
A study was made between 1979 and 1983 on physical, productivity and reproduction characteristics of 193 Baoulé cattle at Avétonou Research and Breeding Station. Height at withers and loin, body length, length of head, chest girth, width of head and loin were measured at 1, 3, 6, 12, 18, 24, 30, 36 and 60 months of age. Age at first calving ranged between 1,111 and 1,278 days. An average calving interval was 558.9±173.4 days (range: 329-1,094 days). Calving rate ranged from 32-61%. Average birth weight of calves varied by month of birth: 13.9 in December to 27.0 kg in September. Weights at various ages including weaning and yearling weights were illustrated. Productivity indexes were produced for each year. The Baoulé cattle were hardy lending themselves to intensive meat production with adaptation to disease-ridden environments such as trypanosomosis and tick-borne diseases.